“Slow science” renaissance: understanding the ecology, natural history and demography of a highly endemic Mygalomorph spider from Argentina - Ferretti, Nelson Edgardo (2023)
“Slow science” approaches to understanding many aspects of the biology of species have declined over recent decades, despite the critical importance of these studies to conservation biology. This approach has been recently developed to study the natural history of an endemic and threatened mygalomorph spider from Australia in order to address future conservation issues. Here, we present a “slow science” study to unveil the demography, ecology and natural history of a potentially threatened species of migid trapdoor spider from mountainous grasslands in central Argentina. Calathotarsus fangioi Ferretti, Soresi, González & Arnedo, 2019 (Migidae) have a highly fragmented distribution in the eastern mountainous belt (Tandilia) from Buenos Aires province, in a landscape largely cleared for agriculture, livestock and tourism. The conservation significance of Mygalomorphae has long been recognized, and these spiders remain a flagship group for terrestrial invertebrate conservation in many countries. By studying growth rates, life spans, recruitment, natural history, dispersal and other aspects of population and individual health, we aim gradually to uncover the population dynamics of a discrete natural population. In this work, we summarize natural history data for a parcel of 98 individual trapdoor spiders marked initially following 44 months of monitoring and highlight preliminary demographic trends and biological observations related with reproductive period, courtship behavior, egg sacs and dispersion.